Model Pendidikan Karakter di SMK Melalui Program Pengembangan Diri dan Kultur Sekolah - Amat Jaedun; Sutarto Sutarto; Ikhwanuddin Ikhwanuddin (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This study aimed to: (1) describe the best practices on the implementation of character education in Vocational High School models through self-development program, and (2) describe the best practices on the implementation of character education in Vocational High School models through school culture. The study was conducted through case studies at SMK N 2 Depok Sleman, SMK N 2 Wonosari, and SMK N 1 Bantul. This study employed quantitative and qualitative approaches (mix-methods). The data was collected using questionnaires, interviews, participant observation, and documentation. The data was analysed using the descriptive technique, both quantitative and qualitative. The results showed: (1) The implementation of scouting activities at SMK 2 Wonosari was intensive and very effective in instilling or developing the students’ positive characters, (2) The role of school culture in the character education at SMK 2 Depok Sleman focused on seven-characters values (3) The implementation of the Honesty Canteen at SMK 1 Bantul was effective to develop the value of honesty among the students.